High sensitivity liquid surface deformation sensor based on cascaded Bowknot Type Tapers. Issue 10 (7th June 2019) - Shuai, Shaojie; Xiao, Yike; Deng, Huitong; Sun, Zhiqiang; Gong, Jiaqi; Liu, Zexu; Fang, Jiahao; Yu, Jing; Lang, Tingting; Zhao, Chunliu; Shen, Changyu
ABSTRACT: A liquid surface deformation sensor with high sensitivity based on a Mach–Zehnder interferometer (MZI) was demonstrated. The MZI was constructed by cascading two Bowknot Type Tapers (BTTs) with an interval of 1.0 cm. As the liquid surface changes gradually from the position higher than the optical fibre to a position lower than the optical fibre, the external environment of the optical fibre changes gradually from the liquid to air, this will result in a change of the interference of the MZI. By measuring the intensity variations of the resonant wavelength, the liquid surface deformation in the range from 0 to 5.22 mm can be determined with a high sensitivity of 0.99 dB/mm.